Microwave bandpass filters with quarter-wavelength resonators - Sun, Bing. (2013)
This report presents the proposal and synthesis design of microwave bandpass filters with quarter-wavelength (λ⁄4) stepped-impedance resonators (SIRs) on the basis of immittance inverters. Firstly, the bandpass prototype filter is proposed with identical terminations and alternative immittance inverters. After that the prototype network is transformed to bandpass filter network based on coupled quarter-wavelength stepped-impedance resonators. The dimension of each coupling stage and resonators are determined through extracting design parameters. At the same time, a pair of transmission zeros are introduced with cross coupling implemented, which results in a better filter selectivity. Finally, a 2nd-order and a 4th-order Chebyshev bandpass filters are constituted. Both of them operate at 2.4 GHz with 10% fractional band widths. Simulated results are presented in the end.